Swedish courts’ evaluations of interpreter-mediated child investigative interviews - Ernberg, Emelie (Child maltreatment, 2023)
Children can need the help of an interpreter if they are victims of a crime and need to be forensically interviewed in another language. Recent findings from practitioners raise concerns about the state of interpreter-mediated interviews with children. The current study aimed to explore how Swedish criminal courts reason when assessing interpreter-mediated and interpreter-absent (with children who are not fluent in Swedish) child investigative interviews. We conducted qualitative and descriptive analyses of written court verdicts involving 108 child victims who were evaluated to need an interpreter during their investigative interview. The courts frequently discussed issues regarding possible misinterpretations, language difficulties, and confusion. These perceived deficiencies in the interviews were often mentioned as a cause for assessing the child’s testimony with caution and, in some cases, as lowering the evidential value of the child interview. Possible implications for children’s legal rights are discussed.